Optimalisasi Open-Mindedness Character Strengths dalam Upaya Meningkatkan Critical Thinking Siswa Guna Mencapai Profil Pelajar Pancasila - Herdiansyah, Diki; Naini, Rohmatus; Hanifah Puteri, Nurul; Hamza, Qurrota Ayunin (Prodi Bimbingan Konseling FKIP UNDANA, 2024)
This study aims to examine the optimization of open-mindedness characteristics in enhancing students' critical thinking skills, in alignment with the achievement of the Profil Pelajar Pancasila (Pancasila Student Profile). Using a qualitative approach with a literature review methodology, the research identifies various theories and practices that link open-mindedness with critical thinking. The analysis reveals that open-mindedness, which includes openness to new ideas and diverse perspectives, plays a crucial role in developing critical thinking skills. Students with this characteristic tend to be better at evaluating arguments, considering multiple viewpoints, and making more informed decisions. Furthermore, this study highlights strategies for fostering open-mindedness within the educational context, particularly in guidance and counseling, such as group discussions, project-based learning, role-playing, simulation games, and the integration of technology-based tools like augmented reality (AR) and virtual reality (VR). The findings are expected to contribute to the development of a more effective and inclusive curriculum, supporting the achievement of national educational goals to produce a generation that is not only knowledgeable but also character-driven and competitive. This study recommends the need for training educators and counselors to apply methods that foster the development of open-mindedness among students..